PROFESIONALISME GURU DALAM PENERAPAN KURIKULUM MERDEKA BELAJAR PADA MATA PELAJARAN PAI - Rahma, Silvia; Munawwir; Rabiyatul Adawiyah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
This study discusses teacher professionalism in implementing the Merdeka Curriculum in Islamic Religious Education (PAI) subjects. The Merdeka Curriculum is designed to provide flexibility to educators in developing learner-centered learning, thus requiring teachers to be more adaptive, innovative, and highly competent. However, in its implementation, teachers face various challenges, such as limited resources, lack of teacher readiness in adjusting learning methods, and paradigm shifts in learning evaluation. Therefore, an appropriate strategy is needed to improve teacher professionalism in order to optimize their role in the Merdeka Curriculum-based education system. This research uses the literature study method by analyzing various relevant reference sources to identify challenges and solutions in improving the professionalism of PAI teachers. The results show that strengthening continuous training, improving pedagogical and professional competencies, and supporting comprehensive education policies are the main factors in supporting the effective implementation of the Merdeka Curriculum. With the right strategy, PAI teachers are expected to be better prepared to develop innovative learning that meets the needs of students.